Invertebrate genetic models of amyotrophic lateral sclerosis - Zhou, LiJun; Xu, RenShi (Frontiers in Molecular Neuroscience, 2024)
Amyotrophic lateral sclerosis (ALS) is a common adult-onset neurodegenerative disease characterized by the progressive death of motor neurons in the cerebral cortex, brain stem, and spinal cord. The exact mechanisms underlying the pathogenesis of ALS remain unclear. The current consensus regarding the pathogenesis of ALS suggests that the interaction between genetic susceptibility and harmful environmental factors is a promising cause of ALS onset. The investigation of putative harmful environmental factors has been the subject of several ongoing studies, but the use of transgenic animal models to study ALS has provided valuable information on the onset of ALS. Here, we review the current common invertebrate genetic models used to study the pathology, pathophysiology, and pathogenesis of ALS. The considerations of the usage, advantages, disadvantages, costs, and availability of each invertebrate model will also be discussed.